A model of the Marxist rent theory - Debarshi Das (University of Massachusetts, Department of Economics, 2018)
This paper presents an interpretation of Marx's rent theory. The three forms of rent, differential rent of type one and two, and absolute rent, have been elaborated and represented through algebra. Marx situated his theory in an agrarian economy characterised by the capitalist mode of production. Such conditions are not present in the agrarian economy of India, yet one can still borrow Marx's analytical tools, the paper argues, to understand the contemporary agrarian India. Some observations on Indian agrarian economy have been offered in the end.
Keywords: 330; Marx; absolute rent; organic composition of capital; landed property